Law of universal gravitation:
F = GMm/r²
F = gravitational force, G = gravitational constant, M & m = masses of the objects, r = distance between the objects
F is proportional to both M and m:
F ∝ M, F ∝ m
F is proportional to the inverse square of r:
F ∝ 1/r²
Calculate the scaling factor of F due to the change in M:
k₁ = 2M/M = 2
Calculate the scaling factor of F due to the change in m:
k₂ = 2m/m = 2
Calculate the scaling factor of F due to the change in r:
k₃ = 1/(4r/r)² = 1/16
Multiply the original force F by the scaling factors to obtain the new force:
Fk₁k₂k₃
= F(2)(2)(1/16)
= F/4